Design and data analysis of a wearable basketball training posture measurement system based on multifunctional conjugated polymer composite materials - Hu, Yunzhang; Huang, He (Molecular & cellular biomechanics, 2024)
Conjugated materials in basketball training are specific polymers included in sportswear to record and analyze player motions, helping to improve skills and prevent injuries by offering an in-depth analysis of the biomechanics and movements of athletes during training sessions. These materials provide basketball players with lightweight, long-lasting, and versatile qualities, offering comfortable gear that precisely monitors movements, complementing their training requirements for enhanced performance and technique improvement. This article describes creating and examining a novel wearable basketball conditioning posture assessment system called DMAS4B (Dynamic Motion Analysis System for Basketball). The technology includes sophisticated computer vision algorithms (CVA-Kalman Fusion Algorithm), Inertial Measurement Units (IMUs), and versatile, conjugated polymer composite materials. These materials, strategically positioned within specially developed sportswear, enable real-time tracking and evaluation of basketball player locations during training sessions. DMAS4B includes gathering detailed body movement data and focusing on essential basketball skills like shooting technique, dribbling stance, and defensive alignments. The collected data is delivered wirelessly to the MotionPro+ Basketball Analytics Software, a specialized platform for thorough analysis and visualization. The ability of IMUs, multifunctional conjugated polymer composites, and computer vision algorithms to work together to record and analyze basketball player movements precisely is demonstrated in this study. The system’s implementation seeks to connect traditional training methods with advanced technology, providing athletes and coaches instant and thorough feedback on posture accuracy, balance, and mastery of techniques. The comprehensive examination of data collected from DMAS4B offers a novel method to improve basketball training programs, enhance player performance, and reduce the likelihood of injuries. In addition, the flexible character of this technology provides a foundation for possible use in various sports, transforming customised training methods worldwide.